The Effect of Working Capital, Operating Costs, and Business Revenue on the Net Profit - Pakpahan, Jiyad Faqih; Syafina , Laylan; Yanti, Nursantri (LifeSciFi, 2026)
In the current competitive business environment, understanding the key financial factors that drive profitability is critical for effective management and decision-making. This study investigates the influence of working capital, business revenue, and operating cost on the net profit. The study employs multiple linear regression analysis using IBM SPSS software to assess the relationships between the variables. The findings reveal that working capital, business revenue, and operating expenses simultaneously have a significant impact on net profit. However, the partial test results show that only business revenue has a statistically significant effect on net profit, while working capital and operating expenses do not demonstrate a significant influence. These results indicate that the cooperative’s profitability is more strongly driven by its ability to generate revenue from business activities rather than by the level of working capital or operating expenses alone. The study concludes that increasing and maintaining stable business revenue plays a key role in improving financial performance. The implications of this research suggest that cooperative managers should focus on strengthening revenue-generating activities and business operations to support sustainable profitability and long-term financial stability.